Explorando a diversidade do comércio justo na economia social - Benjamin Huybrechts; Jacques Defourny (Ciências Sociais Unisinos)
Fair trade (FT) organizations have been quite early taken as examples of social enterprises (SE) and have contributed to the shaping of the SE concept. The goal of this article is to examine more deeply, both at a conceptual and at an empirical level, to what extent FT organizations can be considered as social enterprises. First, we introduce different theoretical frameworks of SE and examine FT in the context of each of these frameworks. In a second step, we use an empirical study on fair trade social enterprises (FTSEs) across four European countries to illustrate and deepen the links between FT and SE, focusing on the goals and the governance structures of FTSEs. It appears that all FTSEs combine in some way economic, social and sometimes also political goals. FTSEs are thus in line with the "hybrid goal" nature of SEs. FTSEs' governance is also quite specific and often innovative in terms of organizational architecture and stakeholders' involvement. Some FTSEs are closer to the European - participatory - approach to social enterprise, while others are closer to US - individual - approaches. Finally, the governance structures of FTSEs seem to reflect quite well their mix of goals.